2017
DOI: 10.1017/s1431927617012399
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Study of the Anti-inflammatory Effects of Triptolide on Rheumatoid Arthritis Fibroblast-like Synoviocytes

Abstract: High-resolution atomic force microscopy (AFM) was used for the in situ evaluation of the anti-inflammatory effects of triptolide on rheumatoid arthritis (RA) fibroblast-like synoviocytes (FLS) to understand the anti-RA effects of triptolide, based on the morphological and biophysical changes observed in RA-FLS. RA-FLS have been reported to play a primary role in inflammatory bone destruction during the development of RA and thus are regarded as an important target for RA treatment. Triptolide pretreatment sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Many studies showed the Tripterygium ingredients have the properties to promote FLS apoptosis and cell cycle arrest and inhibit FLS autophagy ( Xu, 2013 ; Xu et al., 2013 ; Lei et al., 2015 ; Su et al., 2017 ; Wong et al., 2019 ). It may be relevant to the increased expression of Bax/Bcl-2, Caspase-3, Caspase-9, and regulating by Ca2+/calmodulin-dependent protein kinases beta (CaMKK)-AMPK-mTOR signaling pathway.…”
Section: The Role Of Tripterygium Ingredients On Fls and The Moleculementioning
confidence: 99%
“…Many studies showed the Tripterygium ingredients have the properties to promote FLS apoptosis and cell cycle arrest and inhibit FLS autophagy ( Xu, 2013 ; Xu et al., 2013 ; Lei et al., 2015 ; Su et al., 2017 ; Wong et al., 2019 ). It may be relevant to the increased expression of Bax/Bcl-2, Caspase-3, Caspase-9, and regulating by Ca2+/calmodulin-dependent protein kinases beta (CaMKK)-AMPK-mTOR signaling pathway.…”
Section: The Role Of Tripterygium Ingredients On Fls and The Moleculementioning
confidence: 99%
“…The current researches on the mechanism of TPL in the treatment of RA mainly includes the following aspects: Wang et al () applied TPL to collagen‐induced RA mice, suggesting that TPL could improve arthritis symptoms of RA by inhibiting the secretion of inflammatory cytokines by T lymphocytes; Kong et al () proposed that TPL could inhibit the inflammation of RA by blocking the angiogenesis at the inflammatory site; Su, Sun, Ao, and Zhao () proposed that TPL could mediate the apoptosis of fibroblast‐like synoviocytes and inhibit their inflammation to improve the symptoms of RA. Fan et al () found that TPL could inhibit the degree of inflammation through TREM‐1 signaling pathway; Liu et al () proposed that TPL could block RANKL/RANK/OPG signaling pathways in collagen‐induced RA mice to prevent the formation of OCs from OCPs, thereby inhibiting bone destruction of RA.…”
Section: Discussionmentioning
confidence: 99%
“…FLS plays an essential role in the development of synovial inflammation of RA (Li et al, ). Triptolide, celastrol, geniposide, paeoniflorin, clematichinenoside AR, kirenol, tanshinone IIA, bauchampine A, baicalein, 1,7‐dihydroxyl‐3,4‐dimethoxylxanthone, catechin, licochalcone A, luteolin, quercetin, ramosissimin, α‐mangostin, berberine, fissistigmine A, matrine, norisoboldine, sinomenine, tamaractam, caffeic acid, paeonol, chlorogenic acid, and daphnetin have been reported to induce apoptosis of FLS or inhibit its proliferation (Bi, Xin, Gao, Lin, & Qian, ; Chen et al, ; Chen et al, ; Hong et al, ; Hua et al, ; Jie et al, ; Kusunoki et al, ; Li et al, ; Liu et al, ; Liu, Feng, Wang, Zhao, & Li, ; Lou et al, ; Luo et al, ; Pan, Zhu, Lv, & Pei, ; Shu et al, ; Su et al, ; Su, Sun, Ao, & Zhao, ; Sun et al, ; Sun, Ding, & Yao, ; Sung et al, ; Tang, Wei, & Wang, ; Wang et al, ; Wang, Jiang, & Sun, ; Wang, Sun, & Jin, ; Xu et al, ; Yang, Dong, & Li, ; Yao et al, ; Yi et al, ; Zhang et al, ; Zhang et al, ; Zheng, Wei, Zhu, & Liu, ; Zhou et al, ; Zuo, Xia, Li, Ou‐Yang, & Chen, ). Some previous researches have shown that betulinic acid, kaempferol, leonurine, oxymatrine, and piperlongumine can inhibit the migration and invasion of FLS in RA models (Li et al, ; Liang et al, ; Liu, Feng, et al, ; Pan et al, ; Sun, Xu, Du, Zhang, & Zhu, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…Some previous researches have shown that betulinic acid, kaempferol, leonurine, oxymatrine, and piperlongumine can inhibit the migration and invasion of FLS in RA models (Li et al, ; Liang et al, ; Liu, Feng, et al, ; Pan et al, ; Sun, Xu, Du, Zhang, & Zhu, ). Triptolide, celastrol, geniposide, paeoniflorin, clematichinenoside AR, glycyrrhetinic acid, kirenol, cucurbitacin E, 1,7‐dihydroxyl‐3,4‐dimethoxylxanthone, calycosin, catechin, cyanidin‐3‐glucoside, quercetin, α‐mangostin, leonurine, norisoboldine, oxymatrine, caffeic acid, paeonol, resveratrol, shikonin, and 3 R ‐(4′‐hydroxyl‐3′‐ O ‐β‐ d ‐glucopyranosyl phenyl)‐dihydro isocoumarin alleviate inflammatory response by inhibiting the release of a variety of proinflammatory factors (e.g., activin A, ciliary neurotrophic factor, and fractalkine) in FLS of RA models (Bi et al, ; Chen et al, ; Deng et al, ; Huang et al, ; Jia et al, ; Li et al, ; Liang et al, ; Lin, Sato, & Ito, ; Liu, Feng, et al, ; Mao, Sun, Pei, & Zhang, ; Su et al, ; Su et al, ; Sun et al, ; Sun et al, ; Sun & Li, ; Sung et al, ; Tang et al, ; Tian, Chen, Gao, Li, & Xie, ; Venkatesha, Astry, Nanjundaiah, Yu, & Moudgil, ; Wang, Sun, & Jin, ; Wei et al, ; Yang et al, ; Yang et al, ; Zhang et al, ; Zheng et al, ; Zuo et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
See 1 more Smart Citation